Layer Number Controllable Molybdenum Disulfide Film Growth and Its Applications in Vertical and Planar Photodetectors - Yu‐Han Huang; Zhi‐Wei Chen; Chao‐Hsin Wu; Po‐Tsung Lee; Shih‐Yen Lin (Advanced Materials Interfaces)
Abstract Wafer‐scale and layered MoS2 films are grown by sulfurizing amorphous MoS2 films deposited on sapphire substrates by using a radio‐frequency sputtering system. To verify the layer numbers of the multi‐layer MoS2 films, atomic layer etchings are adopted. Wafer‐scale MoS2 film growth with good layer number uniformity up to 30 is observed. A vertical device with 20‐layer MoS2 embedded in between Al (bottom) and Au (top) electrodes is fabricated. With different work functions of the metal electrodes, photo‐excited electrons and holes in the MoS2 layer can be separated and form photovoltaic responses. With the insertion of 5 nm MoO3 carrier transport layer between the MoS2 layer and the top Au electrode, enhanced photovoltaic responses are observed for the device. By using graphene as the carrier transport layer and MoS2 as the light absorption layer, avalanche photocurrents are observed for planar MoS2/graphene photoconductive devices. With the assist of the higher electron density in multi‐layer MoS2, an easier compensation in the loss of photo‐excited electrons and therefore, charge neutrality in the MoS2 layer can be maintained. Significant reduction in the rise/fall times from >100 ms. to <10 ms. is also observed for the planar photodetector with 10‐layer MoS2 absorption layer.